Human Spinal Oligodendrogenic Neural Progenitor Cells Promote Functional Recovery After Spinal Cord Injury by Axonal Remyelination and Tissue Sparing. (7th August 2018) - Nagoshi, Narihito; Khazaei, Mohamad; Ahlfors, Jan‐Eric; Ahuja, Christopher S.; Nori, Satoshi; Wang, Jian; Shibata, Shinsuke; Fehlings, Michael G.
Abstract: Cell transplantation therapy utilizing neural precursor cells (NPCs) is a conceptually attractive strategy for traumatic spinal cord injury (SCI) to replace lost cells, remyelinate denuded host axons and promote tissue sparing. However, the number of mature oligodendrocytes that differentiate from typical NPCs remains limited. Herein, we describe a novel approach to bias the differentiation of directly reprogrammed human NPCs (drNPCs) toward a more oligodendrogenic fate (oNPCs) while preserving their tripotency. The oNPCs derived from different lines of human NPCs showed similar characteristics in vitro. To assess the in vivo efficacy of this approach, we used oNPCs derived from drNPCs and transplanted them into a SCI model in immunodeficient Rowett Nude (RNU) rats. The transplanted cells showed significant migration along the rostrocaudal axis and proportionally greater differentiation into oligodendrocytes. These cells promoted perilesional tissue sparing and axonal remyelination, which resulted in recovery of motor function. Moreover, after transplantation of the oNPCs into intact spinal cords of immunodeficient NOD/SCID mice, we detected no evidence of tumor formation even after 5 months of observation. Thus, biasing drNPC differentiation along an oligodendroglial lineage represents a promising approach to promote tissue sparing, axonal remyelination, and neural repair after traumatic SCI.Stem Cells Translational Medicine 2018;7:806–818 Abstract : Oligodendrogenic neural progenitor cells (oNPCs) are tripotent cells biased to differentiate towards a higher proportion of oligodendrocytes compared to conventional NPCs. oNPCs are promising cells to be utilized as cell replacement strategies to treat the injured spinal cord. To generate oNPCs, a patient's own somatic bone marrow cells can be directly reprogrammed to unpatterned NPCs (drNPCs). In the next step, drNPCs are biased towards oNPCs. After transplantation, oNPCs integrate into host tissue and differentiate to oligodendrocytes, neurons, and astrocytes. and are involved in myelination of denuded axons and the preservation of endogenous tissue which results in functional recovery.